Pelestarian Buah Langka sebagai Strategis Resiliensi Masyarakat Menghadapi Perubahan Iklim di Desa Marajai Kabupaten Balangan - Alfajeri, Dodi; Ni'mah; Hayati, Azkiya; Ramadhan, Muhammad Hafi; Usta, Putri Rabiatul; Rahmah, Siti Azizah; Rosmawarni; Nuraini, Dina Aprilia; Kurniawan, Rizky; Sarah, Siti; Maimunah (Prodi Sosiologi FISIP ULM, 2025)
The community service program was implemented in Marajai Village, Halong District, Balangan Regency, South Kalimantan, known for its natural beauty and the existence of local and rare fruits. However, this village faces serious challenges in the form of unpredictable climatic conditions that threaten the sustainability of fruit production. The rare fruits that grow in Marajai Village have high ecological, economic, and cultural value, but their existence is increasingly threatened. This program aims to raise public awareness that local fruits are not only important for meeting daily needs, but also have great potential as leading commodities and tourist attractions, both locally and internationally, thereby increasing income and supporting sustainable village development. The program will run from July 17 to September 11, 2025, using a live-in and participatory approach. With this approach, the community is actively involved in the process of gathering information, identifying problems, and formulating solutions. The results show that the Marajai Village community has adapted and transformed in the face of climate challenges by strengthening the potential of rare fruits, identifying the causes of declining production, and formulating resilience strategies. The strategies implemented include collaborative planting of new seedlings across various parties and strengthening the economic value of rare fruits as village assets. This program emphasizes that community resilience is not only reflected in the ability to adapt ecologically, but also in social and economic innovations based on local potential. Thus, strengthening resilience is a key strategy in maintaining the sustainability of natural resources and the cultural identity of the Marajai Village community.